Constructing on alternative reality: aspects of the work of Stanley Spencer - Grobler, Georg Diederik (My University, 1997)
Through his depiction of the ordinary and the everyday, Stanley Spencer manages to convey an extraordinary vision. This research investigates his visionary intentions as expressed through narrative pictorial devices. The construction of an 'Alternative Reality' in painting relates to the desire to absorb the spectator into an imaginary world of the artist's devising, based largely on his culture-specific environment Through the use of a naturalistic style, Spencer is able to mirror as well as deviate from a straightforward copy of events to arrive at a visual expression of his idiosyncratic views. I will examine how his belief in the redemptive power of art underlies his transfusion of ordinary situations with his unorthodox religious views to the views of W.J.T. Mitchell and James J Elkins on the radical possibilities of narrative in painting are considered in relation to Spencer's method of constructing images and his process of materializing his unified vision. I relate my own work to the above concerns.
DISSERTATION SUBMITIED TO THE DEPARTMENT OF FINE ARTS, FACULTY OF ARTS AT THE UNIVERSITY OF THE WiTWATERSRAND IN PARTIAL FULFILLMENT OF THE REQUIREMENTS FOR THE DEGREE OF MASTER OF ARTS
Keywords: SPENCER, STANLEY, SIR, 1891-1959--CRITICISM AND INTERPRETATION.; NARRATIVE PAINTING, BRITISH.